2010
DOI: 10.7589/0090-3558-46.4.1070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycoplasma Isolated From an Ibex (Capra Ibex) Suffering From Keratoconjunctivitis in Northern Italy

Abstract: ABSTRACT:In 2005 a Mycoplasma species was isolated from ocular-conjunctival swabs from an adult male Alpine ibex (Capra ibex) from the Valle d'Aosta Region, Northern Italy. The animal suffered from bilateral ocular discharge with diffuse inflammation, severe corneal involvement of the left eye and mild corneal opacity of the right eye. Histologic examination revealed a keratoconjunctivitis characterized by lymphocytic and plasmacellular infiltration. Laboratory investigations of the isolate included culture, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This is the first report of M. feriruminatoris presence in wild Alpine ibex in France. We also demonstrated that a previously unidentified isolate collected in Valle d'Aosta (Italy) from an Alpine ibex with severe conjunctivitis, namely 283F08 (Giangaspero et al, 2010), belongs to the M. feriruminatoris species on the basis of its fusA sequence.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…This is the first report of M. feriruminatoris presence in wild Alpine ibex in France. We also demonstrated that a previously unidentified isolate collected in Valle d'Aosta (Italy) from an Alpine ibex with severe conjunctivitis, namely 283F08 (Giangaspero et al, 2010), belongs to the M. feriruminatoris species on the basis of its fusA sequence.…”
Section: Resultsmentioning
confidence: 51%
“…A specific PCR assay was developed to allow rapid and accurate discrimination of this new member of the M. mycoides cluster, for which both PCR/DGGE and MF-dot identification had failed (Giangaspero et al, 2010; Tardy et al, 2012). DNA sequences putatively specific to G5847 T were identified in the Molligen database using the “Comparative Differential query” Toolbox.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations